Beyond Linguistic Similarity: Conceptual-Linguistic Divergence in EFL Authorship Analysis - Amirudin Latif; Fitri Palupi Kusumawati; Eva Faliyanti (Journal of English Education and Entrepreneurship (JEEP), 2026)
Authorship consistency has taken center stage in academic writing today, especially with the rise of AI and digital writing tools. While traditional authorship studies mostly look at linguistic similarities between disputed and genuine texts, the role of conceptual continuity remains largely overlooked in educational settings. This study addresses this gap by examining authorship consistency in EFL academic writing. Using a qualitative forensic linguistic case study, we analyzed one undergraduate thesis abstract (the questioned document) alongside eight known texts written by the same student. The framework combined linguistic profiling—looking at lexical, grammatical, syntactic, and stylistic features—with a conceptual analysis driven by a handwritten abstract reproduction task. Interestingly, the findings revealed a sharp linguistic mismatch between the thesis abstract and the student's usual writing profile. However, the student displayed deep conceptual continuity, flawlessly rebuilding the study's topic, goals, methodology, findings, and conclusions. This striking contrast where language diverges but the core concept aligns is what we define as conceptual-linguistic divergence. Ultimately, this study suggests that educational authorship checks can no longer rely solely on language patterns; they must integrate conceptual evidence, particularly in EFL contexts.